Seasonal changes in VO2max among division Ia collegiate women soccer players - Miller, T. A.; Thierry-Aguilera, R.; Congleton, J. J.; Amendola, A. A.; Clark, M. J.; Crouse, S. F.; Martin, S. M.; Jenkins, O. C. (The Journal of Strength and Conditioning Research, 2007)
Aerobic capacity and body composition were measured at 3 time points over a 1-year period in 26 Division 1A women soccer players from Texas A&M University, in order to determine whether there were seasonal changes in these parameters. Subjects were tested in December, immediately following a 4-month competitive season; in April, following 15 weeks of strength and conditioning; and immediately prior to the start of the regular season in August, following a 12-week summer strength and conditioning program. A periodized strength and conditioning program design was incorporated in order to optimize anaerobic and oxidative capacity immediately prior to the regular competitive season. Significant differences in VO2max were measured between August (49.24 +/- 4.38 ml/kgmin) and December (44.87 +/- 4.61 ml/kgmin). No significant changes in aerobic capacity were found between April (47.43 +/- 4.01 ml/kgmin) and August (49.64 +/- 5.25 ml/kgmin). Significant increases in body fat were measured between August (15.71 +/- 2.92%) and December (18.78 +/- 2.79%), before and after the competitive season, respectively. No significant changes in body fat were found between April (16.24 +/- 2.95%) and August (15.71 +/- 2.92%). The results of this study suggest that decreases in muscle mass over the course of a regular competitive season contribute to decreases in aerobic capacity in collegiate women soccer players. Although it is unknown whether this decrease in muscle mass is the result of inadequate training or a normal adaptation to the physiological demands imposed by soccer, the results of the current study suggest that resistance training volume should be maintained during the competitive season, in order to maintain preseason levels of muscle mass.